Remoción de colorantes en aguas procedentes de la industria textil mediante el uso de biocarbón (2022)
Dyes are a group of pollutants of growing concern due to the toxic effects associated with their presence in the environment and their recalcitrant character to the degradation by using the conventional systems wastewater treatment plants are operating with. In this regard, biochar, considered as a by-product derived from the biomass thermochemical conversion process, is positioned as an attractive alternative due to the physicochemical properties, including the surface area and the functional groups, exhibited by this absorbing material. In the current work, dye definition, classification, properties and the adverse effects produced in the aquatic ecosystems are presented. Additionally, the commonly used water treatment systems are described, focusing on the use of biochar as an alternative technology. Finally, the cost-efficiency relation and the biochar reusability capacity during the pollutant removal process are covered. In this work, new horizons concerning the contribution to the circular economy and the long-awaited sustainable development are opened. Key words: biochar, dyes, removal, reusability, sustainable development, wastewater.